Ultrahydrous stishovite from high-pressure hydrothermal treatment of SiO(2) - Spektor, Kristina (National Academy of Sciences, 2011)
Stishovite (SiO(2) with the rutile structure and octahedrally coordinated silicon) is an important high-pressure mineral. It has previously been considered to be essentially anhydrous. In this study, hydrothermal treatment of silica glass and coesite at 350–550 °C near 10 GPa produces stishovite with significant amounts of H(2)O in its structure. A combination of methodologies (X-ray diffraction, thermal analysis, oxide melt solution calorimetry, secondary ion mass spectrometry, infrared and nuclear magnetic resonance spectroscopy) indicate the presence of 1.3 ± 0.2 wt % H(2)O and NMR suggests that the primary mechanism for the H(2)O uptake is a direct hydrogarnet-like substitution of 4H(+) for Si(4+), with the protons clustered as hydroxyls around a silicon vacancy. This substitution is accompanied by a substantial volume decrease for the system (SiO(2) + H(2)O), although the stishovite expands slightly, and it is only slightly unfavorable in energy. Stishovite could thus be a host for H(2)O at convergent plate boundaries, and in other relatively cool high-pressure environments.